Elana Wilson Rowe, Arctic Governance: Power in cross-border cooperation (Manchester: Manchester University Press, 2018) - Romain Chuffart (Nordicum-Mediterraneum, 2020)
A review of the book: Elana Wilson Rowe, Arctic Governance: Power in cross-border cooperation (Manchester: Manchester University Press, 2018)